OPTIMIZATION TASK OF NAVIGATIONAL AIDS GROUND NETWORK - Ostroumov, Ivan; Kharchenko, Volodymyr; Kuzmenko, Nataliia (Proceedings of National Aviation University (archive), 2018)
Purpose: The represented research results are aimed to formulate an optimization task of ground based navigational aids network in order to improve performance of provided navigational service. Proposed approach is based on iterative process with estimation performance of positioning in each point of airspace and further selection of the most optimal location for new ground facilities. Methods: Represented approach is grounded on analytical and statistical methods of positioning estimation performance, binary integer linear programing theory, and computer-based simulation at verification stage of development. Results: Ground navigational aids network has been represented as a set of geometrical location of standard service volumes in tree-dimensional space. The possible locations for new ground stations were considered together with an existing navigational aids network. The optimal location of new ground stations of navigational aids are result of objective function maximization with specific constraints. Weighted coefficients of linear objective function indicate a volume of predefined performance level of positioning by navigational aids. Results of optimization task solution in terms of linear programming will provide the most optimal location for new ground station within a pool of possible coordinates. Discussion: Formulation of optimization task in terms of binary integer linear programing represents the problem of optimal location search for new navigational aids in one linear objective function and constraints that can be solved by various math methods. Represented results can be implemented during airspace design and in the development of navigational aids network.